Numerical analysis of the dimensional variation in structural ceramic blocks during the drying process (Research, Society and Development, 2021)
Having products with a relatively low production cost, the ceramic industry is a segment with a fundamental participation in the national economy. However, these are industries that, for the most part, have obsolete manufacturing processes, without adequate quality control, and which generate a high waste of resources and low quality of the final product. As one of the steps in the manufacturing process of a ceramic material, drying is defined as the process of reducing the moisture content of a solid by supplying energy. It's a process that involves complex phenomena of heat and mass transfer, as well as dimensional variations, and which, when done incorrectly, causes structural damage to the product, which are the main responsible for the disposal of parts in the ceramic industry. Therefore, it's extremely important to describe the drying process in detail, providing the necessary information for the process to occur properly. Thus, this research aimed, through mathematical modeling and numerical simulation, to analyze the dimensional variation of a structural ceramic block during the drying process, where mathematical models for volume and surface area of the product were adjusted using Statistica® software to the data experimental data obtained in the literature, under different experimental conditions. Results related to the variations of the external and internal surface areas and volume were exposed and analyzed. It can be concluded that the mathematical model chosen was adequately adjusted to the experimental data collected, with a coefficient of determination that was higher than 0.9; and that, despite undergoing dimensional reductions, the studied ceramic block maintained its initial geometry without showing deformations.